Leadership dan Manajemen Menuju Rekonstruksi Sekolah Tinggi Swasta - Bahyati; Aan (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2021)
Leadership is an important element in high school, leadership will determine the basic preparation of the process of realizing the vision of the organization. Meanwhile, management is an activity carried out in a directed, integrated, organized manner, using optimal human resources. Management is an effort in order to realize the vision of the organization, without vision management is a dream that never materializes in reality. There are important elements in leadership and management that must be considered and owned by private universities to make changes. Namely view, appreciate, list, understanding and evaluate which is abbreviated as value. This paper answers: How is the leadership and management of higher education? How is the management of higher education funds? How is the reconstruction of Private Universities?